Study on Depositional Fabric and Environmental Characteristics of Dendrolites in the Cambrian Zhangxia Formation: An Example from the Houziyu Section of Ezhuang Town, Zibo, Shandong Province, Eastern China. (3rd April 2023) - Wang, Xuan; Wang, Ruyue; Bai, Jianping; Zhang, Na; Xing, Haoting; Kamoto, Michael; He, Weiling
Abstract : The dendrolites composed of light gray massive micrite limestone occur at the top of the Cambrian Zhangxia Formation in Houziyu Section, Zibo, Shandong Province. Because it is very difficult to study the genesis of microbial rocks through "the function of diagenesis filter, " this paper analyzes its genetic mechanism by characterizing the sedimentary fabric and formation environment of dendrolites and it is of great significance to study microbial carbonate deposited in geological history in oil exploration. The Cambrian Zhangxia Formation in the Houziyu section is a marine deposit. The macroscopic shrub-like fabric of centimeter scale can be seen on the surface of the tree-shaped stone, with small biological burrows and remnants of calcareous mud components after filling. The microstructure observation shows that the main fabric of the dendrolites is a dark micrite matrix, bright calcite cement, clastic particles, and a calcified cyanobacteria biological community. Detailed supplementary information on the diversity of calcified microorganisms in dendrolites has been made through the study of various types of calcified cyanobacteria and calcified residual substances in the microbial membrane of calcified cyanobacteria in the dendrolites of the study area. It is clear that dendrolites are the product of the calcification of biofilms or microbial mats dominated by cyanobacteria. With the deepening of this kind of research, it is bound to raise the research of microbial carbonate to a new level in China and provide great help to find oil and gas resources in marine strata of microbial origin in China.